THE BEGINNING OF THE EXCAVATIONS AT THE GEGALASHUR 1 (NORTH-EASTERN CAUCASUS) - Simonenko, Anton Anatol'evic; Kulakova, Ekaterina Petrovna; Kuz'minova, Ulia Vladimirovna (History, Archeology and Ethnography of the Caucasus, 2025)
The early Paleolithic archaeological sites of the North-Eastern Caucasus comprise three distinct groups: Ainikab (Ainikab 1 and 2), Mukhkai (Mukhkai 1, 2, and 2a), and Gegalashur (Gegalashur 1, 2, and 3). These sites are situated within the central mountainous region of Central Dagestan, at an approximate elevation of 1500-1600 meters above sea level. They were initially discovered by A.A. Amirkhanov between 2005 and 2007. In 2023, an expedition from the State Historical Museum, under the leadership of A.A. Simonenko, undertook excavations at the previously uninvestigated Gegalashur 1 site. A primary objective of this excavation was to examine the hypsometric level analogous to layer 80 at the Mukhkai 2 site, a context known for its in situ lithic assemblage and associated fauna. The 2023-2024 excavation at Gegalashur 1 yielded a representative collection of lithic artifacts characteristic of the Oldowan tradition. Technical and typological analysis of these materials revealed the presence of various tool categories, including choppers, picks, and scrapers. Notably, the assemblage was dominated by small flakes, with a complete absence of bifacial tools and flakes exceeding 10 centimeters in maximum dimension. These findings support the classification of the materials from cultural horizons 1 and 2 within the “chopper and pick” technocomplex. Furthermore, preliminary paleomagnetic and palynological analyses tentatively suggest that cultural horizons 1 and 2 correlate with the Olduvai subchron and date no earlier than the onset of the Matuyama paleomagnetic epoch. The formation of these horizons is estimated to have occurred between 1.93 and 2.6 Ma.
Keywords: Central Daghestan; Gegalashur 1; Early Paleolithic; Oldowan; chopper; pick; small flake